Nigeria’s Amalgamation, Social (In)Justice and Security Implications - OLADIPO, Temidayo David; BODUNDE , David Oluwafemi (Nigerian Journal of Peace, Development & Humanitarian Affairs, 2024)
Nigeria emerged in 1914 after the colonialists amalgamated the southern and northern protectorates for administrative purposes without negotiation of the conditions of amity between peoples of both sides. However, with independence from British rule on 1st October 1960, come some challenges arising from glueing together peoples with divergent cultures, languages, historical antecedents and religions. Some of these problems have metamorphosed over time to generate serious security issues. Taking into consideration Nigeria’s political history, this paper examines the implications of the welding of diverse peoples with different orientations for Nigeria’s unity, peace and security. The core position of the paper is that amalgamation was accompanied by some inevitable social injustice that arose as a result of coercing unequals together; the consequence is that social injustice in the Nigerian state bred insecurity. This is so because Nigeria, as a result of the amalgamation, was made to become a deeply divided society. This is responsible for entrenching deep fault lines which have engendered violence and thus threatened security in Nigeria. The methodology employed for the study is qualitative in nature and involves critical content analysis of texts, library and archival materials.